If 3 n = 5 and 4 m = 8 , what is the value of 9 n + m ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Fantastic solution!!
marvellous..................... how smart of you.
i like this way, thanks
that was helpful..
wow its great
goooooodd
what a nice prblem
Nice!
nice problem
great
how clever of you
What a great solution
You really clever. I like this (y)
Ótimo, muito obrigada!
Gr8 thnx a lot
Finding 9 n + m is the same as finding the product of 9 n and 9 m .
If we consider the expression 3 n = 5 , we see that raising each side to the second power gives us:
3 2 ⋅ n = 5 2
9 n = 2 5 .
Now that we know the value of 9 n , we focus on finding the value of 9 m . To do so, we must solve for m , which can be done as follows:
4 m = 8
m lo g 2 4 = lo g 2 8
m = lo g 2 4 lo g 2 8
m = 2 3
Now that we know m we can compute 9 m .
9 m = 9 3
9 m = 7 2 9
9 m = 2 7 .
Thus, 9 n + m = 9 n 9 m = 2 5 ⋅ 2 7 = 6 7 5 .
there's given 3^n = 5 and 4^m = 8 => 2^2m =2^3 => 2m =3 so, m = 3/2
now 9^n+m = 3^2n+2m =3^2n.3^2m =(3^n)^2.3^2.(3/2) =5^2.3^3 =25.27 =675
good
8 = 2 3
4 m = ( 2 2 ) m = 2 2 m
4 m = 8 ⇒ 2 2 m = 2 3 ⇒ 2 m = 3
3 n = 5 ⇒ ( 3 n ) 2 = 5 2 ⇒ 3 2 n = 2 5
9 n + m = ( 3 2 ) n + m = 3 2 n + 2 m = 3 2 n × 3 2 m = 2 5 × 3 3 = 6 7 5
I prefer this solution. :)
3 n = 5 4 m = 2 2 ∗ m = 8 so that m = 3 / 2
9 ( n + 3 / 2 ) = 3 2 ∗ ( 3 / 2 + n ) = 3 3 + ( 3 n ) 2 = 3 3 + 5 2 = 6 7 5
Genius solution, but I think there is a typo. it should 3 3 ∗ ( 3 n ) 2 not 3 3 + ( 3 n ) 2
3 n = 5 ,
9 n = ( 3 n ) 2 = 2 5 .
( 2 2 ) m = 2 3 ,
m= 2 3 , so ( 9 m )= 2 7
Hence 9 n + m = 2 5 × 2 7 = 6 7 5
3 n = 5
Taking *ln on both sides* l n 3 n = l n 5
we get n l n 3 = l n 5
and n = l n 3 l n 5
4 m = 2 2 m = 2 3
2 2 m = 2 3
applying the laws of indices, 2 m = 3
and m = 2 3
i.e. 9 l n 3 l n 5 + 2 3
which gives 6 7 5
3 n = 5 ⟹ n = lo g 3 5 and 4 m = 8 ⟹ n = lo g 4 8 .
lo g 4 8 = lo g 4 4 × 2 = lo g 4 4 + lo g 4 2 = 1 + 2 1 = 2 3
⟹ 9 n + m = 9 lo g 3 5 + 2 3 = 9 2 3 × 9 lo g 3 5
9 lo g 3 5 = ( 3 2 ) lo g 3 5 = 3 2 × lo g 3 5 = 3 lo g 3 2 5 = 2 5
⟹ 9 n + m = 9 2 3 × 2 5 = 2 7 × 2 5 = 6 7 5
1 . 4 m = 8
⟹ 2 2 m = 2 3
⟹ 2 m = 3
⟹ m = 2 3
2 . 3 n = 5
⟹ n = l o g 3 5
N o w , 9 n + m
⟹ 3 2 n + m
⟹ 3 2 l o g 3 5 + l o g 3 3 3 / 2
⟹ 3 l o g 3 5 . 3 3 / 2 2
⟹ ( 5 . 3 3 / 2 ) 2
⟹ 2 5 . 3 3
⟹ 2 5 . 2 7
⟹ 6 7 5
First of all, let us modify the original problem a bit:
9 n + m = 3 2 n + 2 m = 3 2 n 3 2 m
Noting that 3 2 n = ( 3 n ) 2 = 2 5 , we can see that the original expression becomes 2 5 ⋅ 3 2 m . This means that all we need to do is to find m .
Let us now take a look at 4 m = 8 . Note that this is equivalent to 2 2 m = 2 3 . Furthermore, by using the fact that l o g x x = 1 , we get
2 2 m = 2 3 ⇒ lo g 2 2 2 m = lo g 2 2 3 ⇒ 2 m = 3 ⇒ m = 2 3
Thus, if we go back to the original expression we will finally get
2 5 ⋅ 3 2 m = 2 5 ⋅ 3 3 = 2 5 ⋅ 2 7 = 6 7 5 .
Or, I could have simply used the fact that 2 2 m = 2 3 ⇒ 2 m = 3 ⇒ m = 2 3 . Silly me.
3 n =5,means n= lo g 3 5
4 m =8,m=4 2 3
9 n + m = 9 lo g 3 5 + 2 3
=675(rounded)
So here it goes. Let us break 9 as the square of 3. The statement 9 to the power (n+m) then becomes 3 to the power (2n+2m). This implies 9 to the power 2n is multiplied by 9 to the power 2m. What we need now are the values of m and n. Look carefully that 4 to the power m is actually 2 to the power 2m and 8 is 2 cubed The bases being equal, we have 2m equal to 3. This gives m =3/2 and 2m = 3. Moreover 3 to the power 2n is actually 3 to the power n multiplied by itself. This implies 5 multiplied by itself(for obvious reasons!). Thus, we are done with finding the required values if not the individual values of m and n respectively! Now 3 to the power (2n+2m) can be written as 3 to the power 2n multiplied by 3 to the power 2m. We have got the value 3 to the pwer 2n which is fortunately the 5 squared and 3 to the power 2m is actually 3 cubed. Thus, here it is. 5 squared multiplied by 3 cubed gives you 675. Solved!
3^{n}=5; 4^{m}=8 => 2^{2m}=8 => 2m=3
9^{n+m}=9^{n} * 9^{m} = 3^{2n} * 3^{2m} = (3^{n})^{2} * 3^{2m} = 5^{2} * 3^{3} = 25*27= 675
The question is 9 n + m , so we can change it as 9 n × 9 m . First, let's find 9 n . 9 n = 9 3 l o g 5 = 9 2 × 9 l o g 5 = ( 9 9 l o g 5 ) 2 = 5 2 = 2 5 Now, for the 9 m 9 m = 9 4 l o g 8 = 9 2 3 × 8 l o g 8 = 9 2 3 = 2 7 So, 9 n × 9 m = 2 5 × 2 7 = 6 7 5
Well there are many ways of approaching this problem. Im my way, there are some basic principles that one should know in order to solve this question.
a^{b+c) = a^b + a^c
Also, you should know that you can substitute 9 for 3 2
So the question asks what is the value of 9 m + n ⟹ 3 2 ( n + m ) ⟹ 3 2 n × 3 2 m
Now its rather easy to solve for 'm' (from the equation 4 m = 8 ) 'm' is equal to 3/2
And we don't actually have solve for 'm', rather because we know that 3 n = 5 , we know that 3 2 n = 2 5 because we square both sides of the equation.
3 2 m ⟹ 3 2 ( 3 / 2 ) ⟹ 2 7
So we want to find 9 m + n ⟹ 3 2 n × 3 2 m ⟹ 2 5 × 2 7 ⟹ 6 7 5
so, 9^n x 9^m = 3^n x 3^n x 3^2m = 5 x 5 x 27 = 675
4^m=2^2m=8=2^3 => m=3/2.
9^(n+m)=9^n.9^m
9^n=3^2n=5^2=25.
9^m=9^(3/2)=27.
25.27=675
We have 3 n = 5 , so 9 n = = ( 3 2 ) n = ( 3 n ) 2 = 2 5 . Also, 4 m = 8 , so m = 2 3 . But note that 9 n + m = 9 n ⋅ 9 m = 2 5 ⋅ 9 2 3 = 2 5 ⋅ 2 7 = 6 7 5 .
9^(n+m) can be written as (3^n)^2 X 9^m which is equal to 5^2 x 9^m since 3^n=5. Hence, result becomes 25 x 9^m. Now since 4^m=8; m=2x1/2 (sq.root2); hence 9^m = 81. Thus result is 25 x 27 i.e. 675.
If 3^n=5,
9^n=25 (squaring on both sides) - (1).
And, since 4^m=8,
2^(2m)=2^(3) (since 4=2^2 & 8=2^3).
Therefore, 2m=3 (f bases are same, exponents can be equated)
=>m=3/2.
We want 9^(n+m)= (9^n) x (9^m)
= (25) x (9^(3/2))
= (25) x {[9^(1/2)]^3}
= (25) x {[3]^3}
= (25) x {27}
= (25) x {25+2}
= 25x25 + 25x2
= 625 + 50
= 675.
9^n+m= 9^n * 9^m=(3^n)^2 * (3^2)^m since 4^m=8 therefore 2^2m=2^3 hence 2m=3 m=1.5 5^2 * 3^(2*1.5)=25 * 27=675
3^n = 5 n(log 3) = (log 5) n= 1.46
4^m=8 2^2m=2^3 2m=3 m=1.5
n+m= 1.46+1.5 = 2.96
9^2.96 =675
Although we cannot determine n, we can determine m. Note that:
4 = 4 1 < 4 + 4 = 8 < 8 + 8 = 4 2
So a reasonable guess for m is 1.5 knowing how a quadratic graph behaves. In fact 4 1 . 5 = 8.
Now note that:
9 m + n = 9 m × 9 n = 9 1 . 5 × 9 n = 2 7 × 9 n (*)
Remark that:
9 n = ( 3 2 ) n = ( 3 n ) 2 = 5 2 = 2 5
Subbing this into (*) gives us that the answer to this question is 2 5 × 2 7 = 6 7 5
De 4 m = 8 temos que:
( 2 2 ) m = 8 ⇒ 2 2 m = 2 3 ⇒ 2 m = 3 ⇒ m = 2 3
Segue que,
9 n + m ⇒ 3 2 n + 2 m ⇒ 3 2 n ⋅ 3 2 m ⇒ 3 n ⋅ 3 n ⋅ 3 3 ⇒ 5 ⋅ 5 ⋅ 2 7 ⇒ 6 7 5
3 n = 5 ⟹ n = lo g 3 5
4 m = 8 ⟹ m = lo g 4 8
∴ 9 m + n = 9 m ⋅ 9 n = 9 lo g 4 8 ⋅ 9 lo g 3 5
= ( 3 2 ) lo g 4 8 ⋅ ( 3 2 ) lo g 3 5 = 3 2 lo g 4 8 ⋅ 3 2 lo g 3 5
= 3 lo g 4 8 2 ⋅ 3 lo g 3 5 2 = 3 2 lo g 4 6 4 ⋅ 3 lo g 3 2 5
= 3 lo g 4 4 3 ⋅ 3 lo g 3 2 5 = 3 3 × 2 5 = 2 7 × 2 5 = 6 7 5
we've 3 n = 5 , and 4 m = 8 , so:
n = l o g 3 ( 5 ) and m = l o g 4 ( 8 ) ,
than :
n + m = l o g 3 ( 5 ) + l o g 4 ( 8 ) = l o g 9 ( 6 7 5 ) = l o g ( 9 ) l o g ( 6 7 5 )
also we've:
x ( l o g ( x ) 1 ) = e because by add log to both sides we've:
l o g ( x ( l o g ( x ) 1 ) ) = l o g ( e )
( l o g ( x ) 1 ) × l o g ( x ) = 1
1 = 1
so:
9 ( l o g 9 ( 6 7 5 ) ) = 9 ( l o g ( 9 ) l o g ( 6 7 5 ) ) = ( 9 ( l o g ( 9 ) 1 ) ) l o g ( 6 7 5 ) = e l o g ( 6 7 5 ) = 6 7 5
Problem Loading...
Note Loading...
Set Loading...
4 m = 8
2 2 m = 2 3
2 m = 3
9 m = 3 2 m = 3 3 = 2 7
3 n = 5
9 n = 3 2 n = ( 3 n ) ∗ ( 3 n ) = 5 ∗ 5 = 2 5
S o ,
9 n + m = ( 9 n ) ∗ ( 9 m ) = 2 5 ∗ 2 7 = 6 7 5